At the Border of the Socio-environmental Conflict: the Rural Way of Life and the Development of Sun and Beach Tourism in Guanacaste, Costa Rica - Hernández, Aurora (2011)
The tourism in Guanacaste has been one of the economical activities with major growing in this region and its economical importance even impacted the growth of the Internal Gross Product of Costa Rica. However, in spite of its natural beauties, Guanacaste offers limitations associated to the same natural conditions like, the six months of dry periods, the pronounced slopings of same hillsides and   the ecological importance of the mountain areas and coastal zones. The social and natural conditions in which the growth of this economical activity has taken place, the appearance of conflicting situations has resulted between communities and developing enterprises. The objective of these pages is to analyze the resulting socio environmental conflicts between the coastal communities and the developing projects in the last 20 years in Guanacaste, Costa Rica. As part of the methodology it has carried out a search in the national press to document the conflicts.  As a result, It has been possible to achieve the systematization of the principal conflicts opened and organized in a typology which lets to a appreciate them among a joint of topics which are affecting the development in Guanacaste.